Union membership and collective bargaining: Trends and determinants - Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2020)
This survey shows that union membership and density as well as bargaining coverage have fallen in most countries and that collective bargaining has become more decentralized over the last decades. However, there is a considerable amount of variation across countries and between different indicators of unionization and collective bargaining. Unionization is found to be related to a large number of structural, cyclical, institutional, and socio-demographic variables. Although changes in the sectoral structure of the economy and the composition of the workforce have played a role, their contribution to union decline seems to be smaller than widely believed. The effect of globalization on unionization and collective bargaining as well as the role of changing attitudes of employees towards unions are not fully clear, but the rise of the informal sector in various parts of the world poses a challenge to union recruitment. Union density and bargaining coverage are related, but the link is far from perfect. A more important predictor of bargaining coverage is the level at which bargaining takes place. Bargaining coverage is usually high and stable in countries with multi-employer bargaining, and the decentralization of bargaining structures in many countries has contributed to the fall in bargaining coverage observed in the last decades. – – Dieser Überblicksartikel zeigt, dass in den letzten Jahrzehnten die Mitgliederzahlen und Organisationsgrade der Gewerkschaften sowie die Tarifbindung in den meisten Ländern zurückgegangen sind und dass Tarifverhandlungssysteme dezentralisierter wurden. Allerdings gibt es große Unterschiede zwischen den Ländern und zwischen verschiedenen Indikatoren von gewerkschaftlicher Mitgliederstärke und Tarifverhandlungssystemen. Es zeigt sich, dass die gewerkschaftliche Mitgliederstärke mit einer Reihe von strukturellen, zyklischen, institutionellen und sozio-demografischen Variablen zusammenhängt. Obwohl Veränderungen in der sektoralen Struktur und der Zusammensetzung der Beschäftigung eine kleine Rolle spielen, ist ihr Betrag zum gewerkschaftlichen Rückgang offenbar geringer als meist vermutet. Die Auswirkungen von Globalisierung auf Gewerkschaften und Tarifverhandlungen und die Rolle veränderter Einstellungen gegenüber Gewerkschaften sind nicht ganz geklärt, aber das Wachstum des informellen Sektors in vielen Teilen der Welt stellt eine Herausforderung für gewerkschaftliche Rekrutierungsbemühungen dar. Der gewerkschaftliche Organisationsgrad und das Ausmaß der Tarifbindung hängen zusammen, doch ist die Beziehung bei weitem nicht perfekt. Ein wichtigerer Prädiktor der Tarifbindung ist die Ebene der Tarifverhandlungen. Die Tarifbindung ist meist in Ländern mit überbetrieblichen Verhandlungen hoch und stabil, und die Dezentralisierung der Verhandlungsstrukturen in vielen Ländern hat zum Rückgang der Tarifbindung in den letzten Jahrzehnten beigetragen.
Keywords: J51; J52; 330; unions; union membership; collective bargaining; decentralization